Robots, Digitalization, and Worker Voice - Filippo Belloc; Gabriel Burdin; Fabio Landini (Global Labor Organization (GLO), 2022)
The interplay between labor institutions and the firm-level adoption of new technologies such as robotics and other advanced digital tools remains poorly understood. Using a cross-sectional sample of more than 20000 European establishments, this paper documents a positive association between shop-floor employee representation (ER) and the utilization of these advanced technologies. We extensively dig into the potential mechanisms driving this correlation by exploiting rich information on the de facto role played by ER bodies in relation to well-defined decision areas of management, such as work organization, dismissals, training and working time. In addition, we conduct a quantitative case study using a panel of Italian firms and exploiting size-contingent policy rules governing the operation of ER bodies in the context of a local-randomization regression discontinuity design. The analysis suggests a positive effect of ER on investments in advanced technologies around the firm size cutoff, although the results are sensitive to the type of technology and specification choices. We also document positive effects on training intensity and process innovation and no evidence of employment losses or changes in the composition of employment. Taken together, our findings cast doubts on the idea that ER discourages technology adoption. On the contrary, ER seems to influence work organization and certain workplace practices in ways that may enhance the complementary between labor and new advanced technologies.
Keywords: J50; O32; O33; 330; Automation; Robots; Digitalization; Unions; Employee Representation; Labor Market Institutions